Application of the Power of Proof Cyber Notary in Indonesia - Christy, Stephanie; Winarsih, Winarsih; Siahaan, Hotma Elisa Irene; Tjempaka, Tjempaka (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
In the era of electronic technology advancement, the concept of cyber notary has challenged the traditional legal framework in making authentic deeds digitally. Updating legal regulations is crucial to ensure that Notary actions in the electronic sphere remain authentic in accordance with the times. Enforcing the validity of legal documents in the electronic context faces challenges, especially in terms of proving their validity and legitimacy in court. In court, legal regulations regulate the procedures for disclosing relevant facts, with valid evidence and special procedures playing an important role. The government has enacted regulations related to Electronic Information and Transactions, although security and regulatory issues are still a concern. The implementation of cyber notary in Indonesia faces a series of problems including the lack of comprehensive regulations, data security challenges, and technological and infrastructure readiness. However, the amendments to Law Number 2 of 2014 concerning the Position of Notary and Law Number 1 of 2024 concerning the amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions provide an important legal basis. Notaries in the provisions of Indonesian civil law have guidelines in the practice of authentic deeds, which are recognized as binding legal evidence and/or can be directly implemented without going through a court and are the final decision that binds all parties to follow it. However, the challenges in facing the implementation of cyber notary in Indonesia, including the lack of specific regulations, data security issues, technological readiness, and social and cultural constraints require joint efforts from the government, related institutions, and the community to create clear regulations, improve data security, and increase public awareness of the benefits and procedures of cyber notary. By overcoming these problems, it is hoped that it can increase the trust and effectiveness of the cyber notary system in Indonesia.